PENGARUH KUALITAS PELAYANAN KADER POSYANDU TERHADAP KEPUASAN IBU BAYI DAN BALITA PADA DESA MAKMUR MULIA KABUPATEN TANAH BUMBU - Penta Lestarini Budiati; Mailiana Mailiana; Diana Hayati (Sekolah Tinggi Ilmu Ekonomi Nasional (STIENAS) Banjarmasin, 2025)
This study aims to analyze the influence of the service quality dimensions of Posyandu cadres on the satisfaction of mothers of infants and toddlers in Makmur Mulia Village, Tanah Bumbu Regency. The five SERVQUAL dimensions tested include tangibles, reliability, responsiveness, assurance, and empathy. The research method used was quantitative, with a survey approach through the distribution of questionnaires to 67 respondents. Data analysis techniques were multiple linear regression and classical assumption tests. The results showed that partially, three variables tangibles, responsiveness, and empathy significantly influenced community satisfaction. Meanwhile, reliability had no significant effect, and assurance had a negative effect. Simultaneously, all five dimensions significantly influenced community satisfaction, with a coefficient of determination (Adjusted R²) of 68.5%. Empathy was the most dominant dimension influencing satisfaction. This study concluded that the quality of Posyandu cadre services generally influences community satisfaction, particularly through a responsive and empathetic approach. These findings are expected to provide input for the sustainable improvement of Posyandu services.